PRODUCCIÓN DE LA PROTEÍNA RECOMBINANTE HUMANA HSC70 Y SU APLICACIÓN EN EL DESARROLLO DE UN SISTEMA DE DETECCIÓN POR ELISA - Espejo Mojica, Ángela Johana; Departamento de Microbiología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2004)
In order to understand how the Heat Shock Proteins (HSPs) are involved in antitumoral immunity activation process, through their release from tumoral  cells and their interaction with dendritic cells (DC), it is necessary to  develop the proper tools for research on those processes. Therefore, our main aim was to produce and purify the recombinant human protein Hsc70 (rh-Hsc70) obtained from E. coli BL21DE3pLysS pET28a(+)/Hsc70 strain and in that way, it can be used at in-vitro studies of its biological functions over DC. On the other hand, an ELISA system was established for detecting and quantifying the Hsc70 in soluble form